Awareness and Participation of Small Retail Businesses in Cashless Transactions: An Empirical Study - CHATTOPADHYAY, Subho; GULATI, Payal; BOSE, Indranil (Management Dynamics in the Knowledge Economy, 2018)
The ambitious drive of the Government of India to transform the Indian economy from a cash-based economy to a cashless economy was contingent in a big way on the people’s acceptance of cashless modes of transactions, adaptability to cashless transactions and change in the transaction behavior of consumers and retailers, besides several other factors. As the small retailers form the bulk of the Indian retail sector, their ability to go cashless, their psychological preparedness and their willingness to adopt cashless transactions become an issue of prime importance in the movement towards cashless. The present study was conducted to assess the awareness of the small retailers regarding the cashless transaction and its modes, to understand their apprehensions and perceived convenience in dealing with a cashless system of the transaction and to measure their extent of participation in cashless transactions. The study was conducted in Bareilly, an important city in the state of Uttar Pradesh, with a population of around ten lakhs. Data for the study was obtained from 117 retailers using a structured questionnaire. The study found that though a significant number of small retailers were aware of the possibility of the cashless transaction and its modes, their frequency of engaging in cashless transactions was abysmally less as compared to that of cash-based transactions. They were found to believe that dealing with cash was easier in comparison to handling cashless transactions. Fear of losing money due to the faulty transaction was found to be a major deterrent in going cashless amongst the small retailers surveyed during the study.